A systematic review of dermatologic manifestations among adult patients with COVID‐19 diagnosis. Issue 2 (19th March 2021) - Schwartzberg, L.N.; Advani, S.; Clancy, D.C.; Lin, A.; Jorizzo, J.L.
Abstract: Background: Infection with COVID‐19 is characterized by respiratory, gastrointestinal and neurologic symptoms. However, limited evidence exists of the involvement of the integumentary system among COVID‐19 patients and evidence suggests that these symptoms may even be the first presenting sign. Objective: To systematically evaluate the literature published on dermatologic signs of COVID‐19 in order to educate doctors about the dermatologic signs of COVID‐19 infection. Methods: Lit COVID, World Health Organization COVID‐19 database and PubMed were searched using terminology to identify adult patients with confirmed COVID‐19 infection and dermatologic manifestations of disease. The last search was completed on 13 July 2020. Results: There were 802 reports found. After exclusion, 20 articles were found with 347 patients with confirmed COVID‐19 infection. Within these articles, 27 different skin signs were reported. Limitations: Limitations of this review include the recency of COVID‐19 infection; so, there are limited published reports and that many reports are not by dermatologists, and so, the cutaneous signs may be misdiagnosed or misdescribed. Conclusion: Dermatologic manifestations of COVID‐19 may be the first presenting sign of infection; so, dermatologists and doctors examining the skin should be aware of the virus's influence on the integumentary system in order to promptly diagnose and treat the infected patients. Abstract : COVID‐19 infection affects multiple organ systems, including the integumentary system. This systematic review explores the reported dermatologic manifestations associated with this infection in adults.